1912 N.J. Laws 365-66 - (:unkn) unknown (My University, 1912)
Ch. 225, 3: A person who attempts to use against another, or who carries, or possesses any instrument or weapon of the kind commonly known as a blackjack, slung-shot, billy, sand-club, sand-bag, metal knuckles, bludgeon, dagger, dirk, dangerous knife, razor, stiletto, revolver, bomb or other high explosive, or any other dangerous or deadly instrument or weapon, with the intent to use the same unlawfully against another is guilty of a high misdemeanor
Keywords: COMMITTING CRIME W/ WEAPON